Analysis of Students' Reasoning Ability in Solving Non-Routine Math Problems in terms of Learning Style - Widya Rizky Zakinah; Siti Inganah; Minatun Nadlifah (Mathematics Education Journal, 2022)
The purpose of this study is to describe students' mathematical reasoning abilities in solving non-routine problems in terms of learning styles. The type of research used is descriptive with qualitative data. The research subjects were students of class XI IPA. The instruments used are questionnaires, non-routine test questions, and interviews. The data to be taken are data on questionnaires, test questions, and interviews. The data obtained will then be analyzed in a descriptive-qualitative way. The results of this study are that 11th-grade students of MA Muhammadiyah 1 Plus Malang, have several learning styles, namely: visual, kinesthetic, and auditory, respectively: 67%️, 25%️, and 8%. Students with visual learning styles have fairly high reasoning abilities by meeting indicators such as 1) being able to present and make mathematical statements in writing well 2) being able to manipulate y-values, and 3) compiling solutions to existing problems. While students with kinesthetic learning styles, students meet reasoning ability indicators, including 1) writing mathematical statements well, and 2) manipulating target functions, then students with auditory learning styles only have one indicator of reasoning ability, namely: 1) creating and finding solutions to trouble well.